2018
DOI: 10.5194/acp-18-1325-2018
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric organochlorine pesticides and polychlorinated biphenyls in urban areas of Nepal: spatial variation, sources, temporal trends, and long-range transport potential

Abstract: Abstract. The study of persistent organic pollutants (POPs) in low-latitude tropical and subtropical urban cities is necessary to assess their local and global impacts on ecosystems and human health. Despite studies on levels of POPs in water, soils, and sediments, analysis of the distribution patterns, seasonality, and sources of POPs in urban regions of Nepal remain limited. Polyurethane foam (PUF)-based passive air samplers were deployed in three major cities in Nepal: Kathmandu (the capital city), Pokhara,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 48 publications
(60 reference statements)
3
6
0
Order By: Relevance
“…Concentrations of POPs in the source region are broadly similar to levels previously reported for Kathmandu, Hetauda, and Lahore (Table ). The similarity suggested that data obtained by XAD-PAS are overall comparable to values derived from PUF-samplers (Table ).…”
Section: Results and Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Concentrations of POPs in the source region are broadly similar to levels previously reported for Kathmandu, Hetauda, and Lahore (Table ). The similarity suggested that data obtained by XAD-PAS are overall comparable to values derived from PUF-samplers (Table ).…”
Section: Results and Discussionsupporting
confidence: 84%
“…Serious pollution with POPs has previously been observed in South Asian countries. For example, extremely high concentrations of DDT and HCHs were found in Kathmandu and Hetauda . Due to the close proximity between Nepal and the Himalayas, it is interesting to know the extent to which high elevations within the Himalayas have become contaminated.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of total PCBs in B1 and B2, 58 and 23 pg m −3 , respectively (sum of congeners reported in Table 2) (Pozo et al, 2011), China: 600-7,600 pg m −3 (Cui et al, 2017), and Bangladesh: 7-1,800 pg m −3 (Nost et al, 2015). They were similar to those reported in Nepal: 1.2-47 pg m −3 (Pokhrel et al, 2018).…”
Section: Urban Concentrations Of Organochlorine Compounds Pahs and Organophosphate Flame Retardantssupporting
confidence: 76%
“…The concentrations of HCB found in the B1 and B2 periods in Barcelona, 25.5 and 5.4 pg m −3 , respectively (Table 2), were generally lower than those found in other urban areas from India: average values of 120-260 pg m −3 (Chakraborty et al, 2010), Bangladesh: 70-685 pg m −3 (Nost et al, 2015), Bosnia Herzegovina: 34 pg m −3 (Lammel et al, 2011), Nepal: 6.3-1,500 pg m −3 (Pokhrel et al, 2018), or China: 261 pg m −3 (Zhang et al, 2010). The concentrations of PeCB, 8.5 and 0.8 pg m −3 in B1 and B2, respectively, were similar to those described in Bosnia Herzegovina, 9.9 pg m −3 (Lammel et al, 2011).…”
Section: Urban Concentrations Of Organochlorine Compounds Pahs and Organophosphate Flame Retardantsmentioning
confidence: 79%